Comparative Statistical Analysis of Geotextile Tensile Strength Using Wide-Width Strip and Grab Test for Soil Reinforcement Applications - Handoko Subawi; Hetty Fadriani (Universitas Negeri Semarang, 2026)
Abstract. The objectives of this study were to compile a database of geotextiles, test for differences in parameter values between the two methods, and develop a regression model to predict Strip Test values from Grab Test data. This study employed a quantitative approach using local products data, global products for comparison, raw test data, standards, and documents from other countries. Statistical analysis used analysis of variance and boxplots due to the wide variation in the commercial data. The findings of this study confirmed that the Wide-Width Strip Test method per ASTM D4595 produces more precise, consistent, and relevant tensile strength data than the Grab Test per ASTM D4632. The Grab/Strip ratio measured ranged from 1.13 to 6.40 and was not constant. The Strip coefficient of variation of 2.4% was almost half that of the Grab at 5.4%. Woven PET has been shown to have a 48% higher tensile strength and <25% lower elongation than woven PP at the same nominal strength, due to the stiffness of PET's aromatic chains. This study proves that there is no universal conversion factor between the two methods. Mandatory soil reinforcement project specifications require ASTM D4595 or ISO 10319 Strip data.